The Clinical Profile and Coronary Artery Findings in Patients with Atrial Fibrillation - Ali Saleh, Saleh; kadhim Khadir, Faris; Al- Alwany, Ameen (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Atrial fibrillation (AF) is a common arrhythmia in daily practice and one of the heart disorders with the highest morbidity and death rates, as it is responsible for a huge number of negative consequences. In our country, there is limited information on the prevalence or natural history of the less well-defined clinical types. Objective: to evaluate the clinical profile and coronary artery findings in atrial fibrillation patients. Patients and Methods: This cross-sectional study was conducted during the period from the first of October 2019 to end of July 2021 at the Iraqi Center for the heart disease at Baghdad Medical City. Included 32 Iraqi patients with atrial fibrillation of both genders. Angiography performed through the femoral Artery approach, Data collected by history, through clinical examination and investigations, using data collection sheet Results: The main type of AF was chronic, (62.5%), Echocardiography findings revealed Systolic dysfunction in 31.1% of patients, Diastolic dysfunction in 37.5%, and both dysfunctions in 6.2%, Left atrium was dilated in 13 (40.6%). Angiographic findings revealed RCA lesion in 13 (40.6%) patients, LCA in 9 (28.1%) while both RCA and LCA lesions present in 3 (9.4%) patients. LAD lesions reported in 10 (31.2%) patients, LCX in 27.8% and LMS in 16.8%. Conclusion: Chronic AF was the more frequent type, Systolic and diastolic dysfunction are frequent among AF patients. RCA was more frequently affected than LCA, LAD was the more affected branch.